Distribution of deep-water corals, sponges, and demersal fisheries landings in Southern California, USA: implications for conservation priorities - Salgado, Enrique J.; Nehasil, Stephanie E.; Etnoyer, Peter J. (PeerJ (San Francisco, CA), 2018)
Deep-sea corals in Southern California are diverse and abundant but subject to multiple stressors, including bottom-contact fisheries using mobile and fixed gear. There is a need for more information on the distribution of these taxa in relation to the distribution of demersal fishing effort, and the distribution of marine protected areas, in order to improve spatial planning. There are many marine managed areas in Southern California, including essential fish habitat (EFH) areas, conservation areas, and a national marine sanctuary, but specific areas of overlap between bottom fishing and benthic epifauna are poorly known. Groundfish surveys were conducted by the National Marine Fisheries Service using a remotely operated vehicle throughout Southern California between 2003 and 2011 to document abundance and distribution of deep-water rockfish and flatfish to a depth of 500 m. Corals and sponges were also common in these images, providing an opportunity to examine these communities. Analyses of 34,792 still images revealed abundance and diversity of coral and sponge taxa, as well as frequency of fishing debris. The occurrence data were overlaid in a geographic information system with landings data for deep-water (>50 m) demersal fisheries to identify areas of spatial overlap. Corals or sponges were observed in 23% of images. A total of 15 coral genera and six sponge morphotypes were identified. A total of 70 species codes were targeted by deep-water demersal fisheries operating below 50 m for years 2007–2011. A novel priority-setting algorithm was developed to identify areas of high richness, abundance, and fishing intensity (RAFi). Several highly-ranked areas were already protected as EFH (Footprint, Piggy Bank). Other highly-ranked sites (West Catalina Island, San Clemente Island, 9-Mile Bank, Santa Rosa Flats) were encompassed by transient gear restrictions, such as Rockfish conservation areas, but are now recommended for permanent protection by the Pacific Fishery Management Council.